TI_GERICHTE 12.2011.146 vom 4. Juni 2013 , Contratto di vendita e di costruzione di un fondo - difetti - minor valore - TI Tribunale d'appello (2013)
Contratto di vendita e di costruzione di un fondo - difetti - minor valore